2016
DOI: 10.1080/03091929.2016.1158816
|View full text |Cite
|
Sign up to set email alerts
|

On the mechanism of self gravitating Rossby interfacial waves in proto-stellar accretion discs

Abstract: The dynamical response of edge waves under the influence of self-gravity is examined in an idealized two-dimensional model of a proto-stellar disc, characterized in steady state as a rotating vertically infinite cylinder of fluid with constant density except for a single density interface at some radius r 0 . The fluid in basic state is prescribed to rotate with a Keplerian profile Ω k (r) ∼ r −3/2 modified by some additional azimuthal sheared flow. A linear analysis shows that there are two azimuthally propag… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Therefore, we expect that the evolution of the RWI vortices formed in our calculations almost never changes even in the 3D frameworks. The effect of self-gravity prevents the onset of the RWI (Lovelace & Hohlfeld 2013;Yellin-Bergovoy et al 2016). However, once the RWI vortex is formed, there are possibilities that self-gravity can help the vortex survive for a long time .…”
Section: Other Physical Effectsmentioning
confidence: 99%
“…Therefore, we expect that the evolution of the RWI vortices formed in our calculations almost never changes even in the 3D frameworks. The effect of self-gravity prevents the onset of the RWI (Lovelace & Hohlfeld 2013;Yellin-Bergovoy et al 2016). However, once the RWI vortex is formed, there are possibilities that self-gravity can help the vortex survive for a long time .…”
Section: Other Physical Effectsmentioning
confidence: 99%
“…citet-ZhuBaruteau2016 have shown that disc self-gravity weakens the vortex development at artificial density bumps. Lovelace & Hohlfeld (2013) and recently Yellin-Bergovoy, Heifetz, & Umurhan (2016), however, have shown that the disc self-gravity should be included in the RWI simulations for discs with the Toomre parameter Q < Qcrit = (1/h), where h is the geometric aspect ratio (here G = 1 code unit is applied, see details in the next section). For a flatdisc-surface geometry with h = 0.05 this corresponds to Qcrit = 20.…”
Section: Introductionmentioning
confidence: 99%
“…A very similar form of the above equation, which included self-gravity term as well, was obtained in the cylindrical coordinate system for proto-stellar accretion disks by Yellin-Bergovoy, Heifetz, and Umurhan 28 . In the absence of gravity, the above equation will produce a "vorticity-density wave" (which becomes a pure vorticity wave when ρ 1 = ρ 2 ): (2.21) shows that shear too, along with gravity, is affected by the variations in density.…”
Section: 21)mentioning
confidence: 74%
“…Umurhan 28 (they have obtained the cylindrical coordinate version, which is more relevant for accretion disks). We intend to understand the generation mechanism of shear-density waves, which is not yet properly understood.…”
Section: 21)mentioning
confidence: 99%